Controlled synthesis of low-molecular-weight polyethylene waxes by titanium-biphenolate-ethylaluminum sesquichloride based catalyst systems - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Applied Polymer Science, 2007)
Soluble complexes of titanium(IV) bearing sterically hindered biphenols, such as biphenol, 1,1'-methylene di-2-naphthol, 2,2'-methylene bis(4-chlorophenol), 2,2'-methylene bis(6-tert-butyl-4-ethyl phenol), and 2,2' ethylidene bis(4,6-di-tert-butyl phenol), were prepared and characterized. These catalyst precursors, formulated as [Ti((OO)-O-boolean AND)X-2], were active in the polymerization of ethylene at high temperatures in combination with ethylaluminum sesquichloride as a cocatalyst. The ultra-low-molecular-weight polyethylenes (PEs) were linear and crystalline and displayed narrow polydispersities. The catalytic polymerization leading to PE waxes in this reaction exhibited unique properties that have potential applications in surface coatings and adhesive formulations. (c) 2007 Wiley Periodicals, Inc.
Keywords: Catalysts; polyethylene (PE); synthesis; Ziegler-Natta polymerization

MgBr2-mediated ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated aldehydes and ketones with 1,3-dienes - Chavan, Subhash P.; Ethiraj, Krishna S.; Dantale, Shubhada W. (Synthetic Communications, 2007)
A facile, mild, and efficient methodology for the ionic Diels-Alder reaction of acetals of alpha,beta-unsaturated ketones and aldehydes as dienophiles with various 1,3- dienes employing MgBr2 as the Lewis acid catalyst to furnish corresponding Diels-Alder adducts at ambient temperature is described.
Keywords: acetals; Catalysts; Diels-Alder reactions; dienes

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Hydrated clay for catalyst removal in copper mediated atom transfer radical polymerization(a) - Munirasu, Selvaraj; Deshpande, Ashwini; Baskaran, Durairaj (Macromolecular Rapid Communications, 2008)
A simple method has been described to remove catalyst from the copper mediated atom transfer radical polymerization (ATRP) of benzyl methacrylate and methyl methacrylate in anisole at 25 degrees C using hydrated natural clay (sodium montmorillonite, Na-clay). The method consists of (1) addition of hydrated clay (CU(I/)clay approximate to 5 wt.-%) either during or after the polymerization, (2) oxidation of catalyst complex by exposing the terminated reaction mixture in air, and (3) filtration to obtain catalyst free polymer solution. A strong coordination of CuBr-ligand complex onto hydrated clay (10 wt.-%
Keywords: Atom transfer radical polymerization (ATRP); Catalysts; clay; selectivity; synthesis

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas

Cu-II-exchanged montmorillonite K10 clay-catalyzed direct carboxylation of terminal alkynes with carbon dioxide - Aher, Ravindra D.; Gade, Madhuri H.; Reddy, R. Santhosh; Sudalai, Arumugam (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
A new, simple and straight-forward protocol for direct carboxylation of terminal alkynes has been developed using Cu-II-montmorillonite K10 clay as a heterogeneous catalyst and CO2 as the C1 carbon feedstock. Also coupling of terminal alkynes with CO2 (1 atm) in the presence of alkyl halides has been achieved under the same reaction conditions, thereby providing access to a variety of functionalized alkyl-2-alkynoates in high yields.
Keywords: Alkyl esters; Alkyne C-H activation; Carbon dioxide activation; Carboxylation; Catalysts; Montmorillonite clays

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel

Synthesis of non-toxic triethyl citrate plasticizer by esterification of renewable citric acid using modified zeolite - Nandiwale, Kakasaheb Y.; Borikar, Sanjay P.; Bokade, Vijay V. (Clean-Soil Air Water, 2015)
Triethyl citrate (TEC), a non-toxic plasticizer, was synthesized by esterification of renewable citric acid (CA, from entire waste of oranges) with ethanol over modified H-ZSM-5 (HZ-5) zeolite. Different micro-meso composites (M-HZ-5) with varying crystallinities were prepared by alkaline treatment of HZ-5. M-HZ-5(0.6) (87% crystallinity) was observed to be a potential and environmentally benign catalyst with 96% CA conversion, 64% TEC selectivity (61.44% TEC yield), and a reusability of six cycles. The probable catalytic mechanism of esterification was also proposed.
Keywords: Biowaste; Catalysts; green chemistry; Micro-mesopre composites; reusability

Preparation of MgO supported platinum nanoparticle catalyst using toluene dispersed platinum sol - Seth, J.; Nepak, D.; Chaudhari, V. R.; Prasad, B.L.V. (Applied Surface Science, 2017)
An effective way of anchoring Pt nanoparticles on MgO using toluene dispersed platinum nanoparticles (Pt-NPs) as one of the ingredient is demonstrated. The usage of particles dispersed in toluene allows the retention of size and size distribution of preformed Pt-NPs even after deposition on MgO support with high active surface area, which is crucial for heterogeneous catalysis. The catalyst thus prepared, displayed selective hydrogenation of cinnamaldehyde to cinnamyl alcohol with high turn on frequency (TOF − 105 h−1) with respect to the total Pt content. We attribute this efficient catalytic performance to the uniform distribution and deposition of Pt on the active MgO support and its better accessible surface as evidenced by the cyclic-voltammetry results.
Keywords: catalysis; Catalysts; cyclic voltammetry; Deposition; Magnesia; Nanoparticles; sol-gel process

Catalytic activity of CuFe2O4 spinel oxide for liquid-phase oxidation of cinnamyl alcohol - Dange, Rutvija M.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
CuFe2O4 spinel oxide catalyst was synthesized by sol-gel and co-precipitation methods for liquid phase oxidation of Cinnamyl alcohol (CnOH) to Cinnamaldehydes (CnHO) using tert-Butyl hydroperoxide (TBHP) as oxidising agent. Spinel oxide catalyst was characterized by different techniques such as X-ray diffraction (XRD), N-2 adsorption-desorption, BET surface area, and X-ray photoelectron spectroscopy (XPS) to understand the structural, physical properties and oxidation state of the catalyst. The result shows that catalyst prepared by sol-gel method was found higher surface area and smaller crystalline size than co-precipitation method. XPS data confirm the formation of Cu2+ in the spinel which helps to improve the catalytic activity of oxidation. This reaction follows radical mechanism, and exhibited 76.7 % of CnOH conversion and 68.4 % of CnHO, and 24.8 % benzaldehyde (benzald) selectivity using TBHP at 60 degrees C. Kinetic data reveal that 41.2 kJ/mol of activation energy for the reaction. The higher activity of spinel oxide catalyst could be due synergetic effect of spinel (88 %) and oxides (12 %) formed in the catalyst, which helps to provide the oxygen during reaction. The contribution of Cu2+ is higher in sol-gel than co-precipitation, which may provide the better reactivity of catalyst. This work helps to select the effective and cost-effective catalyst for the oxidation of CnOH.
Keywords: Catalysts; Cinnamaldehyde; Cinnamyl Alcohol; Cupper; iron; oxide; spinel

Ligand isomerization driven electrocatalytic switching - Kottaichamy, Alagar Raja; Nazrulla, Mohammed Azeezulla; Parmar, Muskan; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Volokh, Michael; Kotresh, Harish Makri Nimbegondi; Shalom, Menny; Thotiyl, Musthafa Ottakam (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: Catalysts; CO2 reduction; O-2 REDUCTION; oxygen reduction

Selective synthesis of renewable diesel fuel precursors via C-C condensation of biomass-derived furans using a niobium oxide nanocatalyst - Kumar, Mudavath Arun; Swapna, Bhattu; Kalbande, Pavan Narayan; Yalagandula, Lavanya; Singh, Satyapaul A.; Sudarsanam, Putla (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: 2-Methylfuran; Catalysts; dehydration; NB2O5; RANGE ALKANES; solid acid; Valorization